Commitment in painting. (1st April 2017) - Docherty, Thomas
This introductory piece situates Sartre's What is Literature? in a historical and theoretical context. Historically, it points out that it is shaped by issues of collaboration during the Occupation of France in World War II; and, consequently, when writers such as Robert Brasillach are executed for collaboration, it sees literature as a matter of life and death. Theoretically, it addresses the idea of commitment in both writing and painting; and it addresses Sartre's argument in terms advanced by Adorno's criticism of Sartrean ideas of commitment and existentialist choice. Sartre distinguishes prose literature from other arts, including especially painting, and claims that prose, in describing the world, reveals fundamental truths about persons; and, once those truths are revealed, they pose a question to the reader of whether she wishes to change the facts of the world. For Sartre, 'parler, c'est agir'. This is his 'commitment', and it devolves into a choice between capitalism and communism. Adorno shows that Sartre is interested in choice in merely abstract terms, and not in material and empirical choices that are made. The piece examines the relation between 'parler' and 'agir' specifically in terms of the actions made by and on paintings, to argue that what is really at stake in any contemporary political choice is the radical potential not of prosaic content but of aesthetic form.